Symbols in The Chronicles of Narnia - Gažová, Gabriela, 1982- (2006)
The thesis will trace the use of symbolism in C.S. Lewis's The Chronicles of Narnia. It will look for correspondences between the book's symbols and our world and the Bible to uncover what Lewis called a "hidden story". It will comment on the implications of the symbols with respect to the fairy tale genre of the stories